Leczenie chorych na toczniowe zapalenie nerek - Oko, Andrzej; Czekalski, Stanisław (Przewodnik Lekarza/Guide for GPs, 2009)
The metod of the treatment of lupus nephritis depends on disease activity, kidney function at presentation and on morphological type of glomerulonephritis according to WHO classification. According to these criteria, monotherapy with corticosteroids or in combination with immunosuppressive drugs, like cyclophosphamide, azathioprine, mycophenolate and cyclosporine, should be considered. The first goal of the treatment is to achieve remission using induction therapy. After remission, the treatment should be maintained with lower doses of the drugs or by the conversion to less toxic immunosuppressants. During the therapy, the potential toxicity of the drugs used must be carefully monitored, as well as nephro- and cardioprotective medications should be continued.